Survival and biofilm formation of psychrotolerant bacteria under variable temperature and PH in dairy products - Nouai, Chaima; Mihoubi, Fatima Zahra; Rahmoune, Aya; Benamar, Ibrahim (Laghouat : Université Amar Telidji - Département de biologie, 2025)
This applied study aims to assess the presence of psychrophilic and psychrotrophic flora in three commonly consumed dairy products in Algeria—pasteurized milk, plain yogurt, and fresh cheese—and to explore their physiological and enzymatic characteristics that may affect prod- uct quality and safety during cold storage. The research involved isolating and identifying cold- tolerant microorganisms from these products, evaluating their enzymatic activity (amylase, li- pase, and protease) at different temperatures, and investigating their ability to form biofilms, while also estimating their impact on milk shelf life through microbial prediction tools. To achieve these goals, 27 samples (9 from each product type) were collected from local mar- kets in Laghouat, Algeria. After incubation at 4 ± 1°C, isolates were purified and subjected to a series of microbiological and biochemical tests, including Gram staining, motility, triple sugar iron (TSI), and mannitol fermentation. Enzymatic activity was assessed using specific differen- tial media, and biofilm-forming potential was evaluated using PVC microplate assays. The results revealed that several strains exhibited notable cold-active enzymatic activity and variable abilities to form biofilms, suggesting their significant role in accelerating spoilage and reducing shelf life even under refrigeration conditions. This study shows that temperature and pH significantly affect pasteurized milk stability. Pseudomonas grows rapidly even at 4 °C, while Bacillus becomes critical above 8 °C due to spore germination. Acidifying milk to pH 6.0 reduces their activity, supporting targeted control strategies: rapid cooling for Pseudomonas and moderate acidification for Bacillus. Based on these findings, the study highlights the need for improved monitoring systems in dairy production environments and encourages the adoption of targeted hygienic and preservation strategies to limit the impact of these microorganisms.
Implications for food safety